Blood Glucose Response to Unilateral and Bilateral Resistance Training Among Trained Women - NUR KHAIRUNISA, ABU TALIP; ZULKIFLI, ABDUL KADIR; ZULKIFL, ISMAIL; Shahren, Ahmad Zaidi Adruce; Dayang Siti Aisah, Abang Suhaili (UKM PRESS, 2021)
Exercise selection is one of crucial factors in designing a comprehensive training programme. The exposure of different exercise selection may stimulate the specific adaptation imposed demand. In the construction of any resistance training (RT) programme, it is important to choose whether to apply bilateral (BI) or unilateral (UNI) exercise. The present study aimed to look into the physiological responses of blood glucose (BG) between UNI and BI RT. Quantitative research method was used, RT (UNI versus BI training) as the independent variables whereas BG set as the dependent variable. In order to measure training effects following a single bout of different training intervention (UNI versus BI), a crossover experimental pre and post test design was implemented. A total of sixteen (n = 16) trained women with mean age of 23 (SD = 1.35) years old went through a single bout of RT involved a total body exercise using major muscles group with 80% of 1RM for each protocols (UNI and BI) for 10 repetitions to maximal effort (for 3 sets). Crossover design would be more accurate in exposing different training protocol to a similar characteristic of individuals as compared using different individuals. The results revealed that blood glucose (BG) were statistically changed (p < .001) across times (between PRE to IP, between PRE and 15P as well as between PRE and 30P), and finding shows there is no difference between training protocols (p = .39). Thus, similar responses of UNI and BI RT on BG concentration provides wide selection of exercise method to practitioners specifically to trained women. Future research on UNI versus BI RT could venture onto other types of hormones analysis including insulin, growth hormone and cortisol can be included. Besides, future research should consider a long run study that involve chronic adaptation of RT on human body in order to prevent and alleviate disease. Keywords: Acute response; weight training; exercise protocol; blood sugar